High temperature heat - Treatment (HTHT) for partial mitigation of alkali attack in hardened fly ash geopolymer binders. (June 2020) - Naghizadeh, A.; Ekolu, S.O.; Musonda, I.
Abstract: This study investigated the effect of high temperature heat - treatment (HTHT) on alkali attack resistance of hardened fly ash geopolymer binders. A mix of sodium silicate and sodium hydroxide was used to activate low calcium (Class F) fly ash for preparation of geopolymer mortars, while non – reactive standard silica sand was employed as fine aggregate. Cubes of 50 mm size and 25 × 25 × 285 mm prisms were cast for compressive strength and alkali expansion tests, respectively. The hardened geopolymer mortars were subjected to HTHT for 6 h at various temperatures of 100, 200, 400 or 600 ⁰C. They were then immersed in different solutions comprising water, 1 M, 3 M NaOH and stored at 80 ⁰C for 28 days. Compressive strength and length change measurements were done before and after storage of the high temperature treated samples under water or in the NaOH solutions. Also, analytical studies were conducted using X-ray diffraction and scanning electron microscopy. The results obtained showed that HTHT at 200 ⁰C gave a significantly improved resistance of hardened fly ash geopolymer mortars against alkali attack, reducing expansion by 50 %.